High-intensity interval training among middle-aged and older adults for body composition and muscle strength: A systematic review - Alzar-Teruel, María; Aibar-Almazán, Agustín; Hita-Contreras, Fidel; Carcelén-Fraile, María del Carmen; Martínez-Amat, Antonio; Jiménez-García, José Daniel; Fábrega-Cuadros, Raquel; Castellote-Caballero, Yolanda (Frontiers in Public Health, 2022)
Background The aging of population is leading to the investigation of new options to achieve healthy aging. One of these options is high-intensity interval training (HIIT), although its effects on body composition and muscle strength are currently unclear. The objective of this systematic review is to examine the scientific publications on the effects of HIIT on the body composition and muscle strength of middle-aged and older adults. Methods The search was carried out in the PubMed, Cochrane Plus, Web of Science, CINAHL and SciELO databases without limitation of publication dates. The literature search, data extraction and systematic review were performed following the PRISMA standards and the risk of bias of the selected studies was assessed using the Cochrane Collaboration Risk-of-Bias. Results Initially 520 publications were identified, out of which a total of 8 articles were finally selected to be included in this systematic review. Improvements in body composition were seen in six of the selected items and an increase in muscle strength in seven of the eight. Regarding physical function, improvements were found in both gait speed and balance. Conclusions This systematic review found that HIIT is effective in improving body composition and increasing muscle strength. However, when comparing HIIT to moderate-intensity continuous training, it is not clear that HIIT is more beneficial; a firm conclusion cannot be drawn due to the scarcity of published studies, their variety in methodology and the ambiguity of their results, so it is suggested to carry out more research in this area.